What are we talking about when we talk about entrepreneurship? - Gartner, William B. (Journal of Business Venturing, 1990)
The purpose of this research was to explore the underlying meanings researchers and practitioners have about entrepreneurship and to outline some themes that characterize the major issues and concerns that constitute the debate about entrepreneurship as a field of study. The process used to identify the themes that characterize entrepreneurship took the form of a policy Delphi. This Delphi was constructed as a series of three questionnaires to elicit definitions of entrepreneurship that were then analyzed and evaluated. In the first phase, a one-page questionnaire asking for a definition of entrepreneurship was sent to leading academic researchers in entrepreneurship, to business leaders and to politicians. The first questionnaire asked individuals: What is your definition of entrepreneurship? We received 44 responses (36 from academics, 8 from business leaders and none from politicians) from the 280 individuals whom we invited to participate (a 16% response rate). In phase 2, all of the entrepreneurship definitions from the first questionnaire were typed and sent back with a second questionnaire to the 44 respondents. The second questionnaire was generated through a content analysis of the entrepreneurship definitions. Ninety attributes were identified from the entrepreneurship definitions. The second questionnaire asked participants: How important is each attribute to your definition of entrepreneurship? Participants ranked the attributes from very important to unimportant. Of the 44 participants in phase 2, 41 responded to the second questionnaire (93% response rate). The responses from the second questionnaire were then evaluated and factor analyzed. The factor analysis sought to cluster the 90 attributes into a smaller set of factors (themes). The eight-factor solution was selected. The debate about what constitutes the nature of entrepreneurship can be characterized by these eight themes. The Entrepreneur. The entrepreneur theme is the idea that entrepreneurship involves individuals with unique personality characteristics and abilities. Innovation. The innovation theme is characterized as doing something new as an idea, product, service, market, or technology in a new or established organization. Organization Creation. The organization creation theme described the behaviors involved in creating organizations. Creating Value. This theme articulated the idea that entrepreneurship creates value. Profit or Nonprofit. The profit/nonprofit theme is concerned with whether entrepreneurship involves profit-making organizations only. Growth. At issue in this theme is the importance of growth as a characteristic of entrepreneurship. Uniqueness. This theme suggested that entrepreneurship must involve uniqueness. The Owner-Manager. This theme suggested that entrepreneurship involves individuals who are owners and managers of their businesses. The third phase of the Delphi asked the 41 participants to evaluate and comment on the eight factors generated in the second phase. Of the 41 participants in phase 3, 34 responded to the third questionnaire (83% response rate). Since no one agreed-upon definition of entrepreneurship appeared to emerge from the Delphi process, the researcher undertook a cluster analysis of the responses to the third questionnaire to uncover whether any similarities in viewpoints existed among the participants. The data was cluster analyzed using both hierarchical (complete linkage and single linkage) and K-means clustering techniques. Results from these analyses revealed two distinct clusters. The majority (79%) of the participants were clustered in group 1. The focus of this group seems to be on the characteristics of entrepreneurship. Group 1 looked at what happened in the situation. This group indicated that a situation was entrepreneurial if they could answer “yes” to these questions: Is there an entrepreneur involved? Is there innovation? Is there growth? Is there uniqueness? The other group, group 2, focused on the outcomes of entrepreneurship. Group 2 saw a situation as entrepreneurial only if value was created or if someone gained.